THE EFFECT OF TEACHING GAMES FOR UNDESTANDING (TGFU) MODEL WITH MATHEMATICS MONOPOLY MEDIA ON LEARNING MOTIVATION AND MATHEMATICS LEARNING OUTCOMES OF ELEMENTARY SCHOOL CLASS I STUDENTS - Sari, Destia Anjelina; Rusnilawati, Rusnilawati (Prima: Jurnal Pendidikan Matematika, 2024)
The purpose of this study is to describe the motivation and learning outcomes of mathematics using the Teaching Games for Undestanding (TGfU) model with a monopoly on mathematics. The experimental method with the design used in this research is a one-group pretest-posttest research design. In this design it combines pre-test and post-test by conducting tests on subjects before being given treatment and after being given treatment. The results of the hypothesis test show that the value of Sig. (bilateral) is 0.001, meaning that the value of Sig. (bilateral) < less than 0.05, it can be concluded that H0 is rejected and Ha is accepted, namely the learning motivation of the Teaching Games for Understanding (TGfU) model with monopoly mathematics is better than before applying it. the results of the t-test obtained a tcount of 2,773 with a degree of freedom (df) of 32 and a significance value of 5% ttable was 2.01. So it can be concluded that tcount (2.773) > greater than ttable (2.02) which can be interpreted as a Teaching Games for Understanding (TGfU) model with a math monopoly if H0 is rejected and Ha is accepted, which means the model is better than before applying. F count 45.025 thus we can know that the f table is 4.07. Based on the decision above, Fcount (45.025) > greater than Ftable (4.07). So it can be concluded that H0 is rejected and Ha is accepted, which means that the Teaching Games for Understanding (TGfU) model with monopoly media is better than the Problem Based Learning model assisted by image media.